Kajian Kitosan Sebagai Agens Pengendali Penyakit Busuk Buah Kakao (Phytophthora megakarya L.) - Septiana, Septiana; Dirmawati, Suskandini Ratih; Evizal, Rusdi (Jurnal Agro Industri Perkebunan, 2018)
Indonesia is a cocoa producing country with production of 425 thousand tons per year. However, production continues to decline, among others, caused by Phytopthora megakarya cause of fruit rot disease of cocoa, therefore it is necessary effective control of cacao fruit rot disease. This study aims to determine the effect of chitosan concentration on the growth of P. megakarya cause of fruit rot disease in vitro. The research was conducted at Plant Disease Laboratory, Department of Agrotechnology, Faculty of Agriculture, University of Lampung, from November 2012 to January 2013. V8 media research as a medium of growing P. megakarya.  The workshops are arranged in a complete randomized design (CRD) consisting of (1) V8 media without chitosan (2) V8 media 0,2%, (3) V8 media 0,4%, (4) V8 media 0,6%, (5) ) V8 media 0,8% (6) medium V8 fungicided copper oxide 56%, and replicated six times. The results showed that the colonies growth of P. megakarya 6 days after incubation in V8 media 0,4%, 0,6%, 0,8% more depressed than growth on the V8 without chitosan media.   Keywords: concentration, disease control, in vitro, V8 media